2010
DOI: 10.1161/circresaha.109.204396
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Stimulates 27-Hydroxycholesterol Production and Confers Atheroprotective Effects in Human Primary Macrophages

Abstract: Rationale: The synthetic sphingosine analog FTY720 is undergoing clinical trials as an immunomodulatory compound, acting primarily via sphingosine 1-phosphate receptor activation. Sphingolipid and cholesterol homeostasis are closely connected but whether FTY720 affects atherogenesis in humans is not known. Objective: We examined the effects of FTY720 on the processing of scavenged lipoprotein cholesterol in human primary monocyte-derived macrophages. Methods and Results: FTY720 did not affect cholesterol uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 33 publications
3
26
0
Order By: Relevance
“…Enhanced formation of non-enzymatically produced oxysterols may then result from cellular cholesterol auto-oxidation, as elicited by increased oxidant stress in oxLDL-loaded macrophages. Sterol 27-hydroxylase (CYP27A1), the enzyme responsible for the formation of 27-hydroxycholesterol, is highly expressed in macrophages [30][31][32]. To our knowledge, the formation of 27-hydroxycholesterol upon oxLDL exposure has not been reported before.…”
Section: Discussionmentioning
confidence: 89%
“…Enhanced formation of non-enzymatically produced oxysterols may then result from cellular cholesterol auto-oxidation, as elicited by increased oxidant stress in oxLDL-loaded macrophages. Sterol 27-hydroxylase (CYP27A1), the enzyme responsible for the formation of 27-hydroxycholesterol, is highly expressed in macrophages [30][31][32]. To our knowledge, the formation of 27-hydroxycholesterol upon oxLDL exposure has not been reported before.…”
Section: Discussionmentioning
confidence: 89%
“…Another study reasoned that FTY720-P is transported out of mouse brain and spinal cord endothelial cells by ABCC1 (Mrp1) (Cartwright et al, 2013). Furthermore, FTY720 was implemented to affect the cholesterol balance and increased the ABCA1 mRNA and protein levels in human primary macrophages (Blom et al, 2010). While these conflicting data are not yet resolved experimentally, the most likely explanation is a cell typeand tissue-specific expression and regulation of sphingolipid transport systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they reported that FTY720 reduced plasma concentrations of IFN-γ, IL-6 and TNF-α. More recently, Blom et al reported that FTY720 stimulates 27-hydroxycholesterol production and confers athero-protective effects in human primary macrophages (33). As such, FTY720 protects macrophages from free cholesterol-induced toxicity.…”
Section: Discussionmentioning
confidence: 99%